Home delivery of medications: Community pharmacists' perspectives on the pros and cons of the service - Abu-Farha, Rana; Alzoubi, Karem H.; Alkhawaldeh, Rama; Itani, Rania; Karout, Samar; Mukattash, Tareq; Alefishat, Eman (Frontiers in Public Health, 2022)
Objectives: The main goal of the current study was to investigate pharmacists' perception of home delivery of medications service in Jordan and their willingness to use the service. Method: This cross-sectional observational study was conducted between March -April 2022. The study targeted community pharmacists working at different community pharmacies across Jordan. The study questionnaire was distributed through Facebook to target Jordanian community pharmacists’ groups. Results: Three hundred and twenty-four community pharmacists participated in the study, 75% (n=244) of pharmacists reported being willing to use the home delivery and 274 (84.6%) thought it increases the efficiency of their community pharmacies’ services. Only 129 (39.8%) pharmacists agreed or strongly agreed that unlike in-store service, home delivery of medications is suitable only for OTC but not for prescriptions medications Nearly half the number of participating pharmacists (n= 153, 47.2%) believe that the service is suitable for refill prescriptions but not for new prescriptions. Pharmacists believe that the foremost pros of the service were to continue life-saving medical treatment (n= 249, 76.9%), serve sick, elderly, and disabled patients (n= 241, 74.4%), and decrease congestion at health facilities (n= 228, 70.4%). On the other hand, the cons of this service, as perceived by pharmacists included failing to build a professional relationship with patients (n= 203, 62.7%), and the contribution to communication errors (n= 147, 45.4%). Logistic regression showed that pharmacists who serve 50 patients or more per day were more willing to use the service than those serving less than 50 patients per day (OR= 2.058, P= 0.032). Conclusion: The majority of participating pharmacists in this study were willing to use the service at their community pharmacies, especially those serving a large number of patients per day which may indicate the potential of this service in relieving the pressure on community pharmacies and allowing them to serve more patients efficiently.